2021
DOI: 10.1101/2021.12.24.474081
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Convalescence from prototype SARS-CoV-2 protects Syrian hamsters from disease caused by the Omicron variant

Abstract: The mutation profile of the SARS-CoV-2 Omicron variant poses a concern for naturally acquired and vaccine-induced immunity. We investigated the ability of prior infection with an early SARS-CoV-2, 99.99% identical to Wuhan-Hu-1, to protect against disease caused by the Omicron variant. We established that infection with Omicron in naive Syrian hamsters resulted in a less severe disease than a comparable dose of prototype SARS-CoV-2 (Australia/VIC01/2020), with fewer clinical signs and less weight loss. We pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
24
1
3

Year Published

2022
2022
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(34 citation statements)
references
References 49 publications
6
24
1
3
Order By: Relevance
“…The disease characteristics of the Omicron variant observed here are similar to those reported for other SARS-CoV-2 variants like Alpha, Beta, Kappa and Delta in hamsters by earlier studies except that of the body weight loss [9,19,32,33]. Our finding corroborated with the few recent studies which also reported the limited or negligible body weight loss in hamsters post infection with Omicron variants [22][23][24][25][26]. The age and virus dose can affect the body weight loss and disease severity in hamsters post SARS-CoV-2 infection [20,32].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The disease characteristics of the Omicron variant observed here are similar to those reported for other SARS-CoV-2 variants like Alpha, Beta, Kappa and Delta in hamsters by earlier studies except that of the body weight loss [9,19,32,33]. Our finding corroborated with the few recent studies which also reported the limited or negligible body weight loss in hamsters post infection with Omicron variants [22][23][24][25][26]. The age and virus dose can affect the body weight loss and disease severity in hamsters post SARS-CoV-2 infection [20,32].…”
Section: Discussionsupporting
confidence: 91%
“…The virus titration showed early virus clearance from the nasal turbinates by day 5 and from lungs by day 7. We found no evidence that Omicron produce less severe lung disease or more predilection to upper respiratory tract in comparison to lung as reported earlier [20,22,23,24].…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…56,57 Omicron has also been found to be less infective in the lung and cause less severe disease in a Syrian hamster model. 58,59 The decrease in severe disease is also consistent with preliminary clinical and epidemiological evidence that had emerged by the time of this manuscript's submission, suggesting that patients had less severe disease in South Africa. 60 Reduced severe disease in South Africa may be due to a particularly high degree of seroprevalence in South Africa as a result of prior infection and vaccination of the vulnerable population.…”
Section: Discussionsupporting
confidence: 80%